How a resort solves financial crisis in pandemic era? / Yusep Windhu Ari Wibowo - Ari Wibowo, Yusep Windhu (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This study identified and explored the strategies developed by a resort in Lampung Province - Indonesia for surviving in the financial crisis during Covid-19 pandemic. This qualitative study collected data from an in-depth interview with the Resort's General Manager, which were analyzed inductively. The resort focused its survival strategies on financial aspects. This study contributes to enriching the strategies for mitigating the disastrous impacts of the Covid-19 pandemic on the resort business.